Work Caused Musculoskeletal Disorders in Health Professionals (Journal of Health Sciences, 2021)
Introduction: Work-related musculoskeletal disorders (WRMSDs) are the most common work-related diseases and describe a wide range of degenerative and inflammatory conditions affecting blood vessels, peripheral nerves, joints, ligaments, tendons, and muscles. WRMSDs are becoming an increasing problem in modern society. They are the second biggest cause of short-term or temporary incapacity for work just following a cold. At the workplace, health professionals represent a very vulnerable category in terms of musculoskeletal disorders (MSDs) development. It is estimated that almost one-third of all cases of absence from work among health care professionals are related to MSDs. Studies also show that a large number of health professionals report the occurrence of MSDs in one or more regions of the body, with a problem with the lower back being one of the most common.Methods: This article presents a non-experimental (qualitative) research, or a scientific review of the published literaturewhere the databases were reviewed in which the keywords for the review were: MSDs, work, health, intervention program,and ergonomics. Various databases were used in the preparation of this article, including PubMed, Google Scholar, Medline, Hrčak, Dabar, Science Direct, and Science Citation.Results: The results include a review and analysis of eighteen published scientific articles in the period 2001-2020. The studies published in these articles has been conducted in the United States, Australia, Switzerland, Portugal, Slovenia, Turkey, China, Nigeria, Israel, Tunisia, Iran, Croatia, Taiwan, Bangladesh, Serbia, Macedonia, and Greece.Conclusion: This article should indicate the magnitude of the problems of WRMSDs in health professionals and that this topic is an inexhaustible and very interesting basis for further studies by current and future researchers to create strategies for the prevention and treatment of this disorder and to eliminate its causes.